Amartya Sen’s Defense of Human Rights and the Challenge of Bentham - Habibi, Don A. (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2014)
This essay explores the foundation problem in human rights theory by examining the criticism of Jeremy Bentham and the response of Amartya Sen. Unlike most defenders of human rights, Sen does not avoid Bentham and the foundation problem; nor does he retreat from the traditional theory that regards human rights as preexisting and universal. Furthermore, Sen also embraces other key aspects of the robust traditional theory, namely that human rights include the full range of positive welfare entitlements. Bentham, who famously denounced natural rights claims as "nonsense upon stilts," was unyielding in his insistence that rights must be legally enacted and enforceable by clearly named rights providers, such as governments. This essay analyzes the debate between these two philosophers and concludes that Bentham's criticisms remain cogent and prescient.